Interrelationships between Skin Structure, Function, and Microbiome of Pregnant Females and Their Newborns: Study Protocol for a Prospective Cohort Study - Doris Wilborn; Jan Kottner; Kathrin Hillmann; Sa Xu; Frank Konietschke; Ulrike Blume-Peytavi (Hindawi Limited, 2021)
Background. Pregnancy leads to several skin changes, but evidence about structural and functional skin changes is scarce. Findings on skin structure and function in children in their first year reveal rapid skin maturation, but evidence indicates that in particular, water holding and transport mechanisms are different from adults. Important questions include whether maternal cutaneous properties predict infant skin condition, and if so, how. This is especially relevant for the skin's microbiome because it closely interacts with the host and is assumed to play a role in many skin diseases. Therefore, the study objective is to explore characteristics of skin and hair of pregnant women and their newborns during pregnancy and in the first six months after delivery and their associations. Methods. The study has an observational longitudinal design. We are recruiting pregnant females between 18 and 45 years using advertisement campaigns in waiting areas of gynecologists and hospital's outpatient services. A final sample size of n = 100 women is the target. We perform noninvasive, standardized skin, hair, and skin microbiome measurements. We establish the baseline visit during pregnancy until at the latest four weeks before delivery. We schedule follow-up visits four weeks and six months after birth for mothers and their newborns. We will calculate descriptive statistical methods using frequencies and associations over time depending on scale levels of the measurements. Discussion. The majority of previous studies that have investigated infants' skin microbiome and its associations used cross-sectional designs and focused on selected characteristics in small samples. In our longitudinal study, we will characterize a broad range of individual and environmental characteristics of mothers and their newborns to evaluate interrelationships with skin parameters and their changes over time. Considering the combination of these multiple variables and levels will allow for a deeper understanding of the complex interrelationship of the newborn's skin maturation. This trial is registered with ClinicalTrials.gov (Identifier: NCT04759924).